Functional composition of epiphyte communities in the Colombian Andes. Issue 12 (30th August 2019) - Agudelo, Claudia Milena; Benavides, Ana Maria; Taylor, Tyeen; Feeley, Kenneth J.; Duque, Alvaro
Abstract: We identify changes in the functional composition of vascular epiphytes along a tropical elevational gradient with the aim of quantifying the role of climate in determining the assembly of epiphyte communities. We measured seven leaf functional traits (leaf area, specific leaf area, leaf dry‐matter content, leaf thickness, force to punch, stomatal density, and potential conductance index) in the 163 most abundant epiphyte species recorded across 10 sites located along an elevational gradient between 60 and 2, 900 m above sea level in the Colombian Andes. We grouped the epiphyte species into seven hierarchical functional groups according to their most characteristic leaf traits. Along the elevational gradient, the two main independent leaf trait dimensions that distinguished community assemblages were defined primarily by leaf area‐photosynthetic (LAPS) and mass‐carbon (LMCS) gradients. Mean annual temperature was the main determinant of species position along LAPS. In contrast, local changes in specific leaf area due to variation in the epiphytes' relative height of attachment was the main determinant of their position along the LMCS. Our findings indicate that epiphytic plant leaves have evolved to optimize and enhance photosynthesis through a leaf area–based strategy and carbon acquisition through investments in construction costs of leaf area per unit of biomass that aim to regulate light capture and tissue development. Given that most studies of plant functional traits neglect vascular epiphytes, our quantification of the multiple dimensions of epiphyte leaf traits greatly augments our understanding of vascular plant function and adaptation to changing environments.